Effect of feeding fermented soybean meal on broiler chickens’ performance: a meta-analysis - Agung Irawan; Adi Ratriyanto; Adib Norma Respati; Niati Ningsih; Rahma Fitriastuti; Wara Pratitis Sabar Suprayogi; Rendi Fathoni Hadi; Wahyu Setyono; Novi Akhirini; Anuraga Jayanegara (Animal Bioscience, 2022)
Objective The present study aimed to quantify the effects of fermented soybean meal (FSBM) on broiler chickens’ performance by employing a meta-analysis approach. Methods A total of 16 studies were included in the database after being systematically selected using a PRISMA protocol. Hedges’ g effect size was used to quantify pooled standardized mean difference (SMD) using random-effects models at 95% confidence intervals (95% CI). Publication bias among studies was computed with Egger’s test and visualized using funnel plots. Results Results indicated that dietary FSBM inclusion increased final body weight (BW) (SMD = 0.586, 95% CI: 0.221 to 0.951, p = 0.002) of broiler chickens, particularly in starter period (SMD = 0.691, 95% CL: 0.149 to 1.233, p = 0.013) while in the finisher period, the effect was weaker (SMD = 0.509, 95% CI: 0.015 to 1.004, p = 0.043). Average daily gain (ADG), feed intake (FI), and feed conversion ratio (FCR) were not affected with FSBM inclusion when compared to control. Subgroup analysis revealed that FI increased in starter period (SMD = 0.582, 95% CI: 0.037 to 1.128, p = 0.036). When considering types of microorganism as moderating variables in the subgroup analysis, we found that Aspergillus oryzae, mixed probiotics+bromelain protease, Bacillus subtilis, and Lactobacillus bacteria significantly increased ADG and FI (p<0.01). Additionally, either Bacillus subtilis+protease or Bacillus subtilis alone decreased FCR (p<0.001). However, meta-regression analysis showed that levels of FSBM inclusion had no effects on final BW (p = 0.502), ADG (p = 0.588), FI (p = 0.861), and FCR (p = 0.462). Conclusion Substituting SBM in broiler chickens’ diet with FSBM improved BW of broiler chickens, especially in the starter period whereas the effects on ADG, FI, and FCR were mostly dependent on microbial strains used for fermentation.